The Effects of Prostaglandin E2 Treatment on the Secretory Function of Mare Corpus Luteum Depends on the Site of Application: An in vivo Study - Piotrowska-Tomala, Katarzyna K.; Jonczyk, Agnieszka W.; Szóstek-Mioduchowska, Anna Z.; Żebrowska, Ewelina; Ferreira-Dias, Graca; Skarzynski, Dariusz J. (Frontiers in Veterinary Science, 2022)
We examined the effect of prostaglandin (PG) E2 on the secretory function of equine corpus luteum (CL), according to the application site: intra-CL injection vs. an intrauterine (intra-U) administration. Moreover, the effect of intra-CL injection vs. intra-U administration of both luteotropic factors: PGE2 and human chorionic gonadotropin (hCG) as a positive control, on CL function was additionally compared. Mares were assigned to the groups (n = 6 per group): (1) an intra-CL saline injection (control); (2) an intra-CL injection of PGE2 (5 mg/ml); (3) an intra-CL injection of hCG (1,500 IU/ml); (4) an intra-U saline administration (control); (5) an intra-U administration of PGE2 (5 mg/5 ml); (6) an intra-U administration of hCG (1,500 IU/5 ml). Progesterone (P4) and PGE2 concentrations were measured in blood plasma samples collected at −2, −1, and 0 (pre-treatment), and at 1, 2, 3, 4, 6, 8, 10, 12, and 24 h after treatments. Moreover, effects of different doses of PGE2 application on the concentration of total PGF2α (PGF2α and its main metabolite 13,14-dihydro-15-keto-prostaglandin F2α– PGFM) was determined. The time point of PGE2, hCG, or saline administration was defined as hour “0” of the experiment. An intra-CL injection of PGE2 increased P4 and PGE2 concentrations between 3 and 4 h or at 3 and 12 h, respectively (p < 0.05). While intra-U administration of PGE2 elevated P4 concentrations between 8 and 24 h, PGE2 was upregulated at 1 h and between 3 and 4 h (p < 0.05). An intra-CL injection of hCG increased P4 concentrations at 1, 6, and 12 h (p < 0.05), while its intra-U administration enhanced P4 and PGE2 concentrations between 1 and 12 h or at 3 h and between 6 and 10 h, respectively (p < 0.05). An application of PGE2, dependently on the dose, supports equine CL function, regardless of the application site, consequently leading to differences in both P4 and PGE2 concentrations in blood plasma.